2015
DOI: 10.3109/08958378.2015.1060279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cardiopulmonary toxicity of exhausts from soy-based biofuels and diesel in healthy and hypertensive rats

Abstract: Increased use of renewable energy sources raise concerns about health effects of new emissions. We analyzed relative cardiopulmonary health effects of exhausts from (1) 100% soy biofuel (B100), (2) 20% soy biofuel + 80% low sulfur petroleum diesel (B20), and (3) 100% petroleum diesel (B0) in rats. Normotensive Wistar–Kyoto (WKY) and spontaneously hypertensive rats were exposed to these three exhausts at 0, 50, 150 and 500 μg/m3, 4 h/day for 2 days or 4 weeks (5 days/week). In addition, WKY rats were exposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…At the animal level, repeated subacute exposure to RF0 and B30 exhausts was not 378 accompanied by apparent toxicity, except a lower weight gain for rats exposed to RF0 379 upstream DPF. The absence of lung tissue injuries in rats exposed to diesel exhausts are in 380 accordance with previous reports showing modest lung adverse effects of chronic soybean 381 (Bass et al, 2015;Finch et al, 2002) or rapeseed oil-derived fuel exposure in rats (Magnusson 382 et al, 2017 concentrations, the number of regulated genes by B30 emissions was higher downstream than 404 upstream the DPF. Such data were rather surprising since an opposite situation was previously observed in cardiac tissue of rats exposed to diesel emissions (Karoui et al, 2019), suggesting 406 some specific tissue response to gas phase of exhaust or to remaining ultrafine PM.…”
Section: Discussionsupporting
confidence: 86%
“…At the animal level, repeated subacute exposure to RF0 and B30 exhausts was not 378 accompanied by apparent toxicity, except a lower weight gain for rats exposed to RF0 379 upstream DPF. The absence of lung tissue injuries in rats exposed to diesel exhausts are in 380 accordance with previous reports showing modest lung adverse effects of chronic soybean 381 (Bass et al, 2015;Finch et al, 2002) or rapeseed oil-derived fuel exposure in rats (Magnusson 382 et al, 2017 concentrations, the number of regulated genes by B30 emissions was higher downstream than 404 upstream the DPF. Such data were rather surprising since an opposite situation was previously observed in cardiac tissue of rats exposed to diesel emissions (Karoui et al, 2019), suggesting 406 some specific tissue response to gas phase of exhaust or to remaining ultrafine PM.…”
Section: Discussionsupporting
confidence: 86%
“…Both mice and rats were used in this study, as they have been shown to exhibit similar toxicological and pulmonary responses to DE exposure [ 35 , 36 ]. Twelve-to-fourteen-week-old male Wistar Kyoto (WKY) rats ( n = 7 per group) were obtained from Charles River Laboratories Inc. (Raleigh, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…WKY rats were exposed to whole DE in whole-body chambers for 4 h/day, 5 days/week, for 1 month to filtered air (FA, 0 μg/m 3 ) control or DE (50 μg/m 3 , 150 μg/m 3 , or 500 μg/m 3 ). These concentrations represent an occupational exposure and are an established model of air pollution-induced cardiopulmonary system [ 36 , 39 , 44 ] and CNS damage [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen dioxide (NO 2 ) levels were obtained by subtracting NO values from total NO x . Further details are provided in previous publications (Mutlu et al,2015; Bass et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…While this suggests the potential for health benefits, the effects of each exhaust might be unique to the organ system examined. For example, biodiesel has been shown to result in acute pulmonary inflammation similar to petroleum diesel (Mehus et al , 2015), but also elevated acute vascular effects (Bass et al , 2015), significant increased liver and lung tissue damage (Shvedova et al , 2013), elevated pulmonary and liver oxidative stress (Shvedova, Yanamala, 2013), and more pronounced pro-inflammatory pulmonary responses (Shvedova, Yanamala, 2013). At present, the impact of biofuel in the brain is largely unknown.…”
Section: Introductionmentioning
confidence: 99%